The effectiveness of the problem-based learning model assisted by stop-motion animation videos in improving the critical thinking abilities of elementary school students - Kaffah, Laila Silmi; Haryono, Haryono; Utanto, Yuli (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
This research aims to evaluate the effectiveness of the problem-based learning model assisted by stop-motion animation videos in enhancing the critical thinking skills of elementary school students. This research is an experimental study utilizing a nonequivalent control group design. The sample was selected using the purposive sampling technique, with the research sample consisting of 20 students from the first class of grade VI at SDN Dadapayam 01 as the experimental group and 20 students from the second class of grade VI at SDN Dadapayam 02 as the control group. Research data were collected, calculated, and analyzed using the SPSS 24 software. Data collection methods included tests, observations, and documentation. The findings indicate a significant difference in the critical thinking abilities of sixth-grade students between SDN Dadapayam 01 and SDN Dadapayam 02 after engaging in social studies lessons using the problem-based learning model assisted by graphic stop-motion animation videos compared to the problem-based learning model assisted by cut-out stop-motion animation videos. The t-test results, with ð›¼ = 5%, reveal a calculated significance value of 0.014, less than 0.05. In conclusion, implementing the problem-based learning model assisted by graphic stop-motion animation videos is more effective than the model-assisted by cut-out stop-motion animation videos. The expected contribution is that the problem-based learning model assisted by stop-motion animation videos can be considered an alternative for educators to implement in student learning.